2-Ethynylperylene and improved synthesis of 3-ethynylperylene. Issue 9 (2nd March 2016) - Chistov, Alexey A.; Kutyakov, Sergey V.; Ustinov, Alexey V.; Aparin, Ilya O.; Glybin, Anton V.; Mikhura, Irina V.; Korshun, Vladimir A.
Graphical abstract: Abstract: 3-Ethynylperylene1, an important precursor for fluorescent dyes, fluorescent nucleosides, and potent nucleoside-based antivirals, has been prepared from perylene on a multigram scale (3 steps, 55% overall yield). A simple synthesis of 2-ethynylperylene2 from perylene (5 steps, 20% yield) has been developed. UV and fluorescence spectra of the ethynylperylenes1 and2 are compared to those of perylene.